Microbial colorants production in stirred-tank bioreactor and their incorporation in an alternative food packaging biomaterial - Oliveira, Fernanda de [UNESP]; Lima, Caio de Azevedo [UNESP]; Lopes, André Moreni; Marques, Daniela de Araújo Viana; Druzian, Janice Izabel; Júnior, Adalberto Pessoa; Santos-Ebinuma, Valéria Carvalho [UNESP] (MDPI, 2020)
Natural colorants from microbial fermentation have gained significant attention in the market to replace the synthetic ones. Talaromyces spp. produce yellow-orange-red colorants, appearing as a potential microorganism to be used for this purpose. In this work, the production of natural colorants by T. amestolkiae in a stirred-tank bioreactor is studied, followed by its application as additives in bio-based films. The effect of the pH-shift control strategy from 4.5 to 8.0 after 96 h of cultivation is evaluated at 500 rpm, resulting in an improvement of natural colorant production, with this increase being more significant for the orange and red ones, both close to 4-fold. Next, the fermented broth containing the colorants is applied to the preparation of cassava starch-based films in order to incorporate functional activity in biodegradable films for food packaging. The presence of fermented broth did not affect the water activity and total solids of biodegradable films as compared with the standard one. In the end, the films are used to pack butter samples (for 45 days) showing excellent results regarding antioxidant activity. It is demonstrated that the presence of natural colorants is obtained by a biotechnology process, which can provide protection against oxidative action, as well as be a functional food additive in food packing biomaterials.
Keywords: Antioxidant; Biodegradable films; Filamentous fungi; Food package; Natural colorants; Stirred-tank bioreactor